ОЦЕНКА СОСТОЯНИЯ РАСПРЕДЕЛЕНИЯ ЕСТЕСТВЕННЫХ РАДИОНУКЛИДОВ В ПОЧВАХ К БЛИЗЛЕЖАЩИМ ТЕХНОГЕННЫМ ОБЪЕКТАМ - Журакулов, А.Р.; Курбонов, Б.И. (SCIENCE and SOCIETY, 2020)
The background radiation situation of the area is estimated by determining the number of natural radionuclides in them. The value of radiation values indicate the degree of contamination of a given facility. Radiation indicators in ecosystems are regulated by international regulatory documents of the ICRP, IAEA, UN, WHO, etc.), including regulatory documents established in the Republic of Uzbekistan (SanPiN, GOST, etc.). According to SanPiN No. 0193-06, the total maximum annual effective dose in excess of the natural background for the population has been established - 1.0 mSv / year.
Keywords: industrial object; radiation situation; natural radionuclides; gamma-ray spectrometric determination; local area; observation point; distribution of natural radionuclides; radionuclide composition; total specific activity; specific effective activity; natural background